2022
DOI: 10.1021/acsami.2c12998
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the “Library” of Metal–Organic Frameworks for Enzyme Biomineralization

Abstract: Metal–organic frameworks (MOFs) are advanced platforms for enzyme immobilization. Enzymes can be entrapped via either diffusion (into pre-formed MOFs) or co-crystallization. Enzyme co-crystallization with specific metals/ligands in the aqueous phase, also known as biomineralization, minimizes the enzyme loss compared to organic phase co-crystallization, removes the size limitation on enzymes and substrates, and can potentially broaden the application of enzyme@MOF composites. However, not all enzymes are stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Such a unique enzyme immobilization approach has been observed and confirmed in several of our recent works. 21,[30][31][32][33][34][35][36] In this communication, we report the case of aq-ZIF. Because urea can only unfold the exposed portion of enzymes (the buried portion is protected by the MOF scaffolds), 21,44 column 3 of Table 1 reports the chance for different lys regions to be exposed (13-32% depending on labelled regions).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Such a unique enzyme immobilization approach has been observed and confirmed in several of our recent works. 21,[30][31][32][33][34][35][36] In this communication, we report the case of aq-ZIF. Because urea can only unfold the exposed portion of enzymes (the buried portion is protected by the MOF scaffolds), 21,44 column 3 of Table 1 reports the chance for different lys regions to be exposed (13-32% depending on labelled regions).…”
mentioning
confidence: 93%
“…16,21,30 We found that the enzyme was confined both on the crystal surface ( partially embedded) and within crystal defects, a condition also discovered in our recent works. 21,[30][31][32][33][34][35][36] We then distinguished the latter from the former using a recently reported urea-perturbation strategy, 21 followed by revealing the backbone dynamics and contact residues of lys in the co-crystal defects. To our best knowledge, this is the first report on experimental unveiling of enzyme dynamics in unstructured artificial compartments.…”
mentioning
confidence: 99%
“…We recently discovered several new combinations of metal ions and ligands to biomineralize enzymes in water with various degrees of crystallinity and packing quality. 35 We have also developed an experimental strategy to probe enzyme backbone dynamics in MOFs via site-directed spin labeling (SDSL)−electron paramagnetic resonance (EPR) spectroscopy and tested it in other MOFs. 36,37 SDSL−EPR probes enzyme dynamics and structural information at the residue level regardless of the complexities caused by the background and heterogeneity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this work, for proof of principle, we apply this strategy to reveal the orientation and dynamics of a model large-substrate enzyme, T4 phage lysozyme (T4L), upon encapsulations in eight MOFs via biomineralization. 35 These MOFs possess various degrees of crystallization (single crystals, multiphase crystals, and amorphous, gel-like crystals) based on the combination of four metal ions and two ligands. We found that the restriction in the motional dynamics of the labeled sites on the surface of T4L increases as the packing quality/ density is increased.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation